Penguatan Kepemimpinan Generasi Z Melalui Pembinaan Lintas Wilayah di Era Industri 4.0 - Kaslam (Program Studi Ilmu Politik bekerjasama Program Studi Hubungan Internasional, Universitas Islam Negeri Alauddin Makassar, 2024)
The era of Industry 4.0 brings new challenges in learning and leadership development for the younger generation, particularly Generation Z, known as digital natives. The Cross Activist Coaching program is a cross-regional initiative designed to strengthen leadership values, life skills, and a growth mindset among students benefiting from the Beasiswa Aktivis Nusantara (BAKTI NUSA) scholarship. This program was conducted across 13 regions, involving 52 student activists from 15 major universities in Indonesia. It emphasizes inclusivity through cross-program and cross-regional collaboration, with intensive interaction between participants and regional managers. Over two days, participants received leadership reinforcement, leadership project development, and guidance in facing global challenges. Evaluations of the program demonstrated improvements in leadership skills, collaboration, and cross-cultural communication among participants. This program is expected to serve as an active learning model that is adaptive and relevant to 21st-century demands.